THE IMPACT OF COMBINATION ANTIHYPERTENSION THERAPY ON THE MAIN PARAMETERS OF STRUCTURAL AND FUNCTIONAL CONDITION OF MYOCARDIUM OF THE LEFT VENTRICLE AND THICKNESS OF “INTIMA-MEDIA” COMPLEX RELATED TO THE PHENOMENON OF SALT-SENSITIVITY IN PATIENTS WITH REFRACTORY ARTERIAL HYPERTENSION - V. V. Skibitsky; E. S. Garkusha; A. V. Fendrikova (Кардиоваскулярная терапия и профилактика, 2015)
Aim. To assess the influence of combination of antihypertension therapy on the main structure-function myocardium condition of the left ventricle (LV), thickness of intima-media (IMT) in patients with refractory arterial hypertension depending on the phenomenon of salt-sensitivity.Material and methods. Totally, 192 patients included with RAH, that after assessment for salt-sensitivity were randomized to groups: 1st group — salt-sensitive patients, receiving inhibitor of angiotensinconverting enzyme (ACEi), dihydropiridine calcium antagonist (DCA), thiazide diuretic (TD) and direct renin inhibitor (DRI) aliskiren (subgroup 1A) or β-adrenoblocker (β-AB) (subgroup 1B); 2 group — salt-resistant patients, receiving ACEi, DCA, TD and aliskiren (subgroup 2A) or β-AB (subgroup 2B). At the baseline and in 48 weeks of treatment the echocardiographic study was performed.Results. Addition of DRI in 1A subgroup helped to reach target values of blood pressure (BP) in 43,3%, and in subgroup 2A — in 70,4% of patients. Usage of β-AB in subgroup 1B led to decrease of BP to target values in 54,3%, and in 2B subgroup — in 50% patients. Usage of DRI in salt-resistant patients helped significantly to regress the LV hypertrophy than in salt-sensitive. Increase of the number of persons with normalized geometry and diastolic function of the LV was comparable in both groups. Usage of β-AB in salt-sensitive and -resistant patients was followed by statistically more significant improvement of structural and functional condition of myocardium of the LV. Normalized geometry of the LV was registered significantly more commonly in slat-sensitive patients. The decrease of IMT was comparable at the background of the usage of both variants of therapy not depending from salt-sensitivity.Conclusion. Usage of DRI as combination therapy led to more significant in salt-resistant than in salt-sensitive patients, antihypertensive effect and LV hypertrophy regress. Prescription of β-AB was followed by BP decrease to target values in comparable number of patients in 1B and 2B subgroups, but had some advantages in hypertrophy regression and normalization of LV myocardium geometry in salt-sensitive patients comparing to salt-resistant.